The Pawn (Rahn) in Local Practice of Massanra Galung of South Sulawesi Society: A Comparative Analysis of Madhhabs - Kamaruddin; Martiana, Andri; Farhah, Ummi; S, Cahaya Rahmadani (Mazahibuna: Jurnal Perbandingan Mazhab, 2023)
The application of massanra galung has become a customary practice within the Bellu Village community. However, its execution has been observed to frequently experience certain deviations from the established regulations. This study aims to examine the application of the concept of Rahn within the context of the massanra galung practice in Bellu Village, situated in Salomekko District, Bone Regency. It was also carried out with the aim of exploring and analyzing the Rahn concept through the lens of the four main schools of thought (madhhabs) in Sunni fiqh. This research is empirical research, and it was conducted using both a phenomenological and a comparative approach. To achieve the outlined aim, data were collected from interviews with six people who practiced massanra galung and from several community leaders. The obtained results showed that within the implementation system of massanra galung in Bellu Village, it is customary for the pledgor to approach the pawn receiver to secure a loan, typically offering their rice field as collateral. It is important to acknowledge that the views of the four madhhabs on certain matters differ, specifically when considering the practice of massanra galung. However, these schools of thought all agree that due to the fulfillment of the pillars and conditions required for massanra galung, the practice is considered valid and permissible according to Islamic law. Regarding the pawn transaction, two parties are considered namely the pawn giver (rāhin) and the pawn receiver (murtahin). It was recommended that efforts aimed at reinforcing the practice of massanra galung should prioritize the enhancement of record-keeping protocols to mitigate potential disputes.